2021
DOI: 10.1093/jmt/thab017
|View full text |Cite
|
Sign up to set email alerts
|

Active Music Therapy Following Acute Stroke: A Single-Arm Repeated Measures Study

Abstract: Experiencing a stroke can lead to difficulties with emotion regulation and mood disorders like depression. It is well documented that poststroke depression (PSD) affects a third of all stroke survivors. Higher levels of depression and depressive symptoms are associated with less efficient use of rehabilitation services, poor functional outcomes, negative impacts on social participation, and increased mortality. Mood in the acute phases of stroke recovery may be a key factor influencing the depression trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Pediatric asthma patients should attract more attention from the public. We found that a number of MT research focused on other diseases such as autism, 18 , 19 neonatal treatment, 20 , 21 emotional regulation, 22 , 23 and mood disorders, 24 , 25 suggesting MT can have a positive therapeutic impact. However, there has been little research on MT for pediatric asthma patients.…”
Section: Discussion and Future Directionsmentioning
confidence: 96%
“…Pediatric asthma patients should attract more attention from the public. We found that a number of MT research focused on other diseases such as autism, 18 , 19 neonatal treatment, 20 , 21 emotional regulation, 22 , 23 and mood disorders, 24 , 25 suggesting MT can have a positive therapeutic impact. However, there has been little research on MT for pediatric asthma patients.…”
Section: Discussion and Future Directionsmentioning
confidence: 96%